Ultra-processed foods and non-alcoholic fatty liver disease: an updated systematic review and dose–response meta-analysis - Zhang, Jinghong; Shu, Long; Chen, Xiaopei (Frontiers in Nutrition, 2025)
BackgroundStudies reported a significant association between ultra-processed food (UPF) consumption and increased risk of non-alcoholic fatty liver disease (NAFLD), but these have produced conflicting results. Thus, we conducted a systematic review and meta-analysis of existing observational studies to ascertain the association between UPF consumption and risk of NAFLD.MethodsWe systematically searched PubMed, Web of Science, Embase and China National Knowledge Infrastructure (CNKI) without language restrictions for eligible studies published from database inception until 31 March 2025. Pooled relative risks (RRs) with 95% confidence intervals (CIs) were estimated using random-effects or fixed-effects models depending on heterogeneity.ResultsOverall, 10 articles involving 513,440 participants and 20,637 NAFLD cases were included. Highest UPF consumption was associated with a 22% increased risk of NAFLD compared to the lowest consumption (RR = 1.22, 95%CI: 1.14–1.31, p < 0.001), with significant heterogeneity (I2 = 78.5%; Pheterogeneity < 0.001). A 10% increment in UPF consumption was associated with a 6% higher risk of NAFLD (RR = 1.06; 95%CI: 1.04–1.09, I2 = 75.9%; p < 0.001). Dose–response analysis showed a linear trend association between UPF consumption and risk of NAFLD (RR = 1.02; 95%CI: 0.98–1.07, Pdose–response = 0.295, Pnonlinearity = 0.541). Subgroup analyses revealed the positive associations between UPF consumption risk of NAFLD in the subgroups of 24-h dietary recalls (RR = 1.35, 95%CI: 1.24–1.46, p < 0.001), cross-sectional studies (RR = 1.29; 95%CI: 1.11–1.31, p = 0.001) and sample size<5,000 (RR = 1.20; 95%CI: 1.02–1.42, p = 0.030), with less evidence of heterogeneity.ConclusionThis study suggests that high UPF consumption is associated with an increased risk of NAFLD, albeit with substantial heterogeneity. Our findings underscore the importance of limiting UPF consumption in the prevention of NAFLD. Future studies with longitudinal designs are required to elucidate underlying mechanisms and confirm causality.